The Influence of Digital Leadership, Empowerment, and Job Crafting on Sustainable Performance through Psychological Ownership: Case Study DPMG Pidie Regency - Husaini Abdullah; Herizal Herizal; Syamsul Akmal; Zalfa Azrina (Jurnal Ekonomi, Manajemen, dan Bisnis, 2026)
This study examines the influence of digital leadership, empowerment, and job crafting on sustainable performance through psychological ownership at the Community and Village Empowerment Agency (DPMG) of Pidie Regency. The research was motivated by public-sector performance challenges related to uneven digital transformation, limited human resources, and the need to strengthen employees' sense of ownership toward organizational goals. A quantitative explanatory design was applied. Data were collected through questionnaires distributed to the entire population of 34 employees and government-contract employees at DPMG Pidie Regency. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS. The measurement model showed acceptable convergent validity and reliability after two psychological ownership indicators were eliminated. The structural model indicated that job crafting had a positive and significant effect on sustainable performance (O = 0.700; t = 2.182; p = 0.030) and psychological ownership (O = 1.197; t = 2.254; p = 0.025). Psychological ownership also had a positive and significant effect on sustainable performance (O = 0.585; t = 6.597; p = 0.000). In contrast, digital leadership and empowerment did not significantly influence either psychological ownership or sustainable performance. The indirect-effect test confirmed that psychological ownership significantly mediated only the relationship between job crafting and sustainable performance. These findings suggest that sustainable performance in local public organizations is more strongly supported by proactive work redesign and employees' psychological attachment than by formal digital leadership or empowerment practices that have not yet been internalized.